Brief Communication: Further summer speedup of Jakobshavn Isbræ - Joughin, I.; Smith, B. E.; Shean, D. E.; Floricioiu, D. (The Cryosphere, 2018)
We have extended the record of flow speed on Jakobshavn Isbræ through the summer of 2013. These new data reveal large seasonal speedups, 30 to 50% greater than previous summers. At a point a few kilometres inland from the terminus, the mean annual speed for 2012 is nearly three times as great as that in the mid-1990s, while the peak summer speeds are more than a factor of four greater. These speeds were achieved as the glacier terminus appears to have retreated to the bottom of an over-deepened basin with a depth of ~ 1300 m below sea level. The terminus is likely to reach the deepest section of the trough within a few decades, after which it could rapidly retreat to the shallower regions ~ 50 km farther upstream, potentially by the end of this century.